2006
DOI: 10.1088/0268-1242/22/1/s25
|View full text |Cite
|
Sign up to set email alerts
|

Low-temperature pre-treatments in a vertical epitaxial reactor with an improved vacuum load-lock chamber

Abstract: Low-temperature (<750 • C) surface preparation for epitaxial growth poses extra challenges for both hardware of a vertical batch epitaxial reactor and chemistry of in situ pre-epi treatments. The vacuum load-lock chamber of the vertical batch tool has been improved to ensure that residual moisture and oxygen concentrations are suppressed to less than 0.1 ppm. Si-based and Cl-based gases or a mixture of these gases are investigated in terms of effectiveness to remove interfacial residual oxygen at low temperatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Subsequently, the wafers were loaded into a quartz boat within the vacuum load-lock chamber with a certain queue time to minimize re-oxidation. The in-situ clean in the furnace was either a low temperature pretreatment clearly below 750°C [6] or a conventional H 2 bake at or above 800°C followed by a low temperature SiGe deposition. Cross-sectional transmission electron microscope (XTEM) was carried out to study the growth morphology of different SiGe channels.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, the wafers were loaded into a quartz boat within the vacuum load-lock chamber with a certain queue time to minimize re-oxidation. The in-situ clean in the furnace was either a low temperature pretreatment clearly below 750°C [6] or a conventional H 2 bake at or above 800°C followed by a low temperature SiGe deposition. Cross-sectional transmission electron microscope (XTEM) was carried out to study the growth morphology of different SiGe channels.…”
Section: Methodsmentioning
confidence: 99%
“…Since temperature ramping requires a long time in a thermally slow batch system the in-situ clean temperature should be close to the deposition temperature. So a low temperature pretreatment clearly below 750°C [6] has a large impact on throughput. Initial results indicated that a low temperature pretreatment has the same cleaning efficiency as a conventional H 2 bake at 800°C.…”
Section: Manufacturabilitymentioning
confidence: 99%
“…Furthermore, the single-wafer process suffers from inferior productivity especially when the growth amount of SEG exceeds 100 nm at temperature lower than 700 • C. Reduced growth rate imposes low throughput and prolonged thermal budget. Few researchers have been interested in and reported about batch process for SEG in order to surmount the drawback [21][22][23][24]. As for the application to SEG diode switches in nextgeneration memories, which requires SEG height larger than 200 nm with low thermal budget, the batch SEG is considered as the most promising solution to guarantee mass productivity.…”
Section: Introductionmentioning
confidence: 99%